Biological Field Stations Promote Science Literacy through Outreach. (26th May 2021) - Struminger, Rhonda; Short, Rachel A; Zarestky, Jill; Vilen, Lauren; Lawing, A Michelle
Abstract: Biological field stations (BFSs) are well positioned through their informal STEM (science, technology, engineering, and mathematics) education programs to improve levels of science literacy and support environmental sustainability. A survey of 223 US BFSs revealed that their outreach programs strive to promote conservation and environmental stewardship in addition to disseminating place-based knowledge and/or skills. In this article, we unpack the educational approaches that BFSs use to engage learners, the aspects of science literacy most often addressed, and the perceived learning outcomes. Most notably, the BFSs reported that their participants develop an interest in and excitement for science, increase or change their knowledge of program topics, identify more with the scientific enterprise, and engage in scientific practices. The results indicate opportunities for BFSs to conduct more rigorous assessments of participant learning and program impact. By focusing on learner engagement, science learning, and participant outcomes, BFSs and other place-based informal education venues can expand their efforts and better support conservation and science learning.